Relationship between Individual Beliefs and Hypertensive Patient Behavior when Performing Blood Pressure Control - Fernandez, GratsiaViktoria; KetutSudiana, I; Widyawati, IkaYuni (International Journal of Psychosocial Rehabilitation, 2020)
The control of blood pressure in the context of hypertension remains an important health problem and finding strategies to overcome it is a worldwide problem. It is generally believed that a person will take actions to prevent, reduce, and control health problems depending on kind of health belief that they have. The purpose of this study is to find out the relation between the individual beliefs and blood pressure control behavior of hypertensive patients. This study used a cross-sectional design. The subjects were hypertensive patients at the primary health center in Kupang, NTT (n = 67). The independent variable was individual beliefs (perceived threat, perceived benefit, perceived barrier, and perceived self-efficacy) and the dependent variable was blood pressure control behavior. In this study, each respondent was interviewed by the researchers using the individual belief questionnaire and the Hypertension Self-Management Behavior Questionnaire (HSMBQ). The data was analyzed using Chi-square analysis. There was a significant relation between individual beliefs and the blood pressure control behavior of hypertensive patients (X2 values all > 3,841). Perceived barriers had the highest estimated value (OR = 28,889) which shows that the perceived barriers have the biggest relation with blood pressure control behavior. The indicators of individual beliefs of perceived threat, perceived benefit, perceived barrier and perceived self-efficacy will influence the behavior of hypertensive patients when they seek to control their blood pressure.